The Status of Glaucous Gulls Larus hyperboreus in the Circumpolar Arctic - Petersen, Aevar; Irons, David B.; Gilchrist, H. Grant; Robertson, Gregory J.; Boertmann, David; Strøm, Hallvard; Gavrilo, Maria; Artukhin, Yuri; Clausen, Daniel S.; Kuletz, Kathy J.; Mallory, Mark L. (ARCTIC, 2015)
The entire world population of the Glaucous Gull Larus hyperboreus breeds in the circumpolar Arctic. Some local populations appear to be declining significanty. In this paper, we summarize the current state of knowledge on Glaucous Gull populations and trends. The total Arctic population is estimated at approximately 171 000 breeding pairs (> 342 000 breeding individuals) distributed among at least 2700 colonies (many not documented). Population declines may be attributable to egg harvest, contaminants, or food shortages, but other factors operating outside the breeding season should not be excluded. We recommend collaborative conservation efforts that will include better population estimates in most countries, as well as standardized monitoring programs. Toute la population mondiale de goélands bourgmestres Larus hyperboreus se reproduit dans l’Arctique circumpolaire. Certaines populations locales semblent diminuer considérablement. Dans cette communication, nous résumons l’état actuel des connaissances sur les populations et les tendances concernant le goéland bourgmestre. La population arctique totale est estimée à environ 171 000 couples reproducteurs (> 342 000 individus reproducteurs) répartis dans au moins 2 700 colonies (dont grand nombre n’ont pas été consignées). Les déclins de population peuvent être attribuables à la récolte des œufs, aux contaminants ou aux pénuries de nourriture, bien qu’il ne faille pas exclure d’autres facteurs ne se rapportant pas à la saison de reproduction. Nous recommandons des efforts de conservation communs qui comprendront de meilleures estimations de population dans la plupart des pays de même que des programmes de surveillance normalisés.